De quoi l’éducation aux médias numériques est-elle la critique ? - Marlène LOICQ (Tic & Société, 2017)
Media education is a complex field articulating research, practices and public policies. It apprehends the media environment in a critical position articulating the study of industries, contents and practices. Since the widespread transition to digital formats, media education has to rethink its critical posture within an institutionalized educational project that is still being defined. This article proposes to extend the scope of a critical media education to particular issues of the digital age.